2016
DOI: 10.1111/beer.12123
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance, female directors and quality of financial information

Abstract: The aim of this study is to examine whether gender diversity on audit committees (hereinafter, ACs) influences financial reporting quality by using panel data of Spanish listed firms. The financial reporting quality of firms is measured by the type of opinion received in the audit report. We estimate various panel data models of audit opinions and control for factors that are traditionally found to impact audit opinions. This study provides evidence to support the hypotheses that the percentage of females on A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 128 publications
(149 reference statements)
4
107
3
1
Order By: Relevance
“…In this regard, Srinidhi et al (2011) suggest that firms with gender-diverse audit committees have higher earnings and better reporting, which in turn enhance the confidence of external auditors in the firms' financial statements. Pucheta-Martínez et al (2016) find that the proportion of female directors, female independent directors on audit committees, and audit committees chaired by women is correlated with the probability of transparency in financial reporting, by disclosing audit reports with uncertainties and possible scope limitation. A recent study conducted by Gull et al (2018) in the French context shows that the presence of women on audit committees is negatively and significantly associated with earnings management.…”
Section: Gender-diverse Audit Committees and Audit Feesmentioning
confidence: 87%
See 1 more Smart Citation
“…In this regard, Srinidhi et al (2011) suggest that firms with gender-diverse audit committees have higher earnings and better reporting, which in turn enhance the confidence of external auditors in the firms' financial statements. Pucheta-Martínez et al (2016) find that the proportion of female directors, female independent directors on audit committees, and audit committees chaired by women is correlated with the probability of transparency in financial reporting, by disclosing audit reports with uncertainties and possible scope limitation. A recent study conducted by Gull et al (2018) in the French context shows that the presence of women on audit committees is negatively and significantly associated with earnings management.…”
Section: Gender-diverse Audit Committees and Audit Feesmentioning
confidence: 87%
“…Pucheta‐Martínez et al. () find that the proportion of female directors, female independent directors on audit committees, and audit committees chaired by women is correlated with the probability of transparency in financial reporting, by disclosing audit reports with uncertainties and possible scope limitation. A recent study conducted by Gull et al.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…For example, women on boards are less likely to manipulate financial reporting and other disclosures (Heminway, 2007), they have a positive effect on the supervision of financial statements and on the board members' behaviour (Schwartz-Ziv, 2011;Abbott et al, 2012). Moreover, a higher percentage of women on audit committees reduces the probability of qualifications due to errors, non-compliance or omission of information (Pucheta-Martínez et al, 2016) and it improves financial reporting quality since the supervision of the financial statements is enhanced (Gul et al, 2008). Hypothesis 1b.…”
Section: Board Gender Diversitymentioning
confidence: 99%
“…There is an increasing number of studies analysing the relevance of female board directors. This is because it has been demonstrated that their presence can improve financial reporting quality and the promotion of good business practices and strategic decisions for companies (Pucheta-Martínez, Bel-Oms, & Olcina-Sempere, 2016;Rogelberg & Rumery, 1996).…”
Section: Female Directors On Corporate Boardsmentioning
confidence: 99%